Fabrication of photocatalyst MgO: CuO composite and enhancement of photocatalytic activity under UV light - Priya, R.; Stanly, S.; Dhanalekshmi, S.B.; Sagadevan, Suresh (IOP Publishing, 2019)
The green synthesis of composites through biological entities such as natural plants, algae, bacteria, fungi, and viruses is regarded to be easy, fast, affordable, low-cost, and environmentally friendly. Therefore, the MgO:CuO composites were synthesized by eco-friendly synthesis method. The MgO:CuO composites were prepared from many fruits of PAGOB (Pomegranate, Apple, Grapes, Orange and Banana) peel extract. The present study is decolourization of methylene blue dye using UV light. The phase purity and crystallite size were characterized and confirmed by x-ray diffraction (XRD) studies. The maximum absorbance was obtained in the 200-800 nm regions with a prominent peak absorbance was observed by UV-vis spectrum. The corresponding band gap for MgO:CuO composite was calculated using Tauc's plot and was found to be 2.2 eV. The textural and surface morphological feature of the synthesized composites were characterized by High-resolution Scanning Electron Microscopy (HR-SEM) and elemental analysis of Composites was analyzed with the help of Energy Dispersive x-ray analysis (EDX). The influence of pH, dye concentration, amount of photocatalyst and intensity of light on the rate of photocatalytic reaction was observed. The results show that the degradation reached 89% under optimum conditions. The resulting MgO:CuO composites and exhibits highly efficient and excellent photocatalytic properties. This property can be utilized to degrade organic contaminants. This concept was shown by degrading methylene blue, which can be observed photometrically. © 2019 IOP Publishing Ltd.